Analysis of badminton smash with a mobile measure device based on accelerometry - Jaitner, T.; Gawin, W. (ISBS - Conference Proceedings Archive (Konstanz), 2007)
A mobile measure device has been developed to measure acceleration of the upper and lower arm segment as well as of the racket. The system consists of three 2D miniature sensors and a PDA that was used to store and transfer data via WLAN. Accelerometric and kinematic data of Badminton smashs of international and national elite Badminton players were collected. The resultant acceleration of the racket showed high correlation with the ball velocity (r=.897). Differences between international and national players can be observed primarily in the mean values and standard deviation of the racket acceleration as well as in the negative acceleration of the lower arm. It is suggested that an abrupt stopping of the lower arm supports the development of high racket acceleration.